Fourier methods in finance - Nevrla, Matěj; Kolman, Marek; Fičura, Milan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
This thesis aims to provide an insight into Fourier transform based techniques utilized in the field of derivative pricing. We discuss mathematical background of Fourier transform techniques and concept of characteristic functions within the probability theory. We analyze three methods for pricing European-style derivatives, namely FFT method, COS method, and CONV method. These methods are examined in cases when the underlying asset price follows geometric Brownian motion, Heston stochastic volatility model, and variance gamma process. Then, we present generalization of COS and CONV method for pricing path-dependent derivatives. In the appendix we also provide introduction to complex analysis.
Vedoucí práce: Marek Kolman
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses